2017
DOI: 10.1002/ptr.5995
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐chelating effect of silymarin in patients with β‐thalassemia major: A crossover randomised control trial

Abstract: This study aimed to determine the potential iron-chelating effects of silymarin in patients with β-thalassemia major receiving standard iron-chelation therapy. We evaluated whether addition of silymarin to standard iron-chelation therapy could improve iron burden markers and liver and cardiac function in these patients, via a placebo-controlled, crossover clinical study. Silymarin (140 mg) or placebo were administered thrice daily to all patients (n = 82) for 12 weeks, and after a 2-week washout period, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
(65 reference statements)
1
6
0
Order By: Relevance
“…We found that ferritin levels were significantly decreased in β‐TI patients after 3 and 6 months of silymarin therapy. This finding is consistent with previous studies that reported iron‐chelating effect of silymarin in combination with desferrioxamine or deferiprone 5‐8 . Additionally, the iron‐chelating potential of silybin, a major bioactive component of silymarin flavonolignan complex, has previously been reported in patients with hereditary hemochromatosis 9 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that ferritin levels were significantly decreased in β‐TI patients after 3 and 6 months of silymarin therapy. This finding is consistent with previous studies that reported iron‐chelating effect of silymarin in combination with desferrioxamine or deferiprone 5‐8 . Additionally, the iron‐chelating potential of silybin, a major bioactive component of silymarin flavonolignan complex, has previously been reported in patients with hereditary hemochromatosis 9 …”
Section: Discussionsupporting
confidence: 92%
“…Many studies have shown a positive association between serum ferritin levels and liver iron concentration. We and others have previously shown that a combination of silymarin and desferoxamine improves liver and cardiac function in β‐thalassemia major patients 5,10 …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The possible antioxidant mechanisms of silymarin include (a) prevention of free radical formation via inhibition of reactive oxygen species (ROS)‐producing enzymes; (b) direct scavenging of free radicals actions; (c) ion chelation (Fe and Cu) in the intestine; (d) promotion of the synthesis of protective molecules (e.g., heat shock proteins, thioredoxin, and sirtuins) that provide protection against stressful stimuli (Surai, ); and (e) activation of antioxidant enzymes such as superoxide dismutase and nonenzymatic pathways, mainly via Nrf2 activation. For example, it has been reported that silymarin markedly increases the expression of superoxide dismutase in the patients with nonalcoholic steatohepatitis (Milosević, Milanović, Abenavoli, & Milić, ; Stiuso et al, ) and decreases the oxidative stress in the β‐thalassemia patients (Darvishi‐Khezri et al, ).…”
Section: Experimental Pharmacologymentioning
confidence: 99%